Unveiling Indonesia’s Challenges in Attracting Foreign Direct Investment: The Case of Apple Inc and the Electronic Manufacturing Industry - Hanna Angel Roring; Jhon Pattinussa; Roy Vincentius Pratikno (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2025)
Foreign Direct Investment (FDI) plays a pivotal role in advancing economic growth, industrial modernization, and technology transfer in emerging economies. This study explores Indonesia’s persistent challenges in attracting high-technology FDI within the electronic manufacturing sector, focusing on the case of Apple Inc. as a reflection of broader policy dynamics. Employing a qualitative case study approach, the research analyzes secondary data from official reports, government publications, and scholarly literature to uncover the intersection between Indonesia’s economic ambitions, political diplomacy, and security considerations. The findings reveal that although Indonesia possesses significant potential—characterized by abundant resources, a large domestic market, and an expanding digital ecosystem—its investment climate remains hindered by bureaucratic inefficiencies, inconsistent regulations, and limited technological infrastructure. The study highlights that Apple Inc., while fulfilling its Local Content Requirement (TKDN) through software-based initiatives such as the Apple Developer Academy, continues to refrain from establishing local manufacturing facilities. This decision underscores the broader structural constraints faced by multinational corporations operating in Indonesia’s regulatory environment. Economically, the research demonstrates that FDI remains central to Indonesia’s goal of transitioning from resource-based exports toward high-value manufacturing. Politically, it shows that FDI functions as an instrument of economic diplomacy, enhancing Indonesia’s international credibility. From a security perspective, strengthening the electronic manufacturing sector through FDI is vital for achieving technological sovereignty and resilience amid global supply chain disruptions. The study concludes that Indonesia’s success in attracting sustainable FDI depends on its ability to harmonize economic liberalization with institutional reform and industrial readiness. Addressing these structural challenges is imperative for Indonesia to fully integrate into the global value chain and achieve its vision under the Making Indonesia 4.0 roadmap.